(untitled) (AYUSHDHARA, 2024)
This review article delves into the intricate concept of Marma points within the framework of Ayurvedic philosophy, with a specific focus on the Katikataruna Marma located in the Prushta region. Marma points, regarded as vital energy centers, house Prana, and hold profound implications for health. The Katikataruna Marma, characterized as a Kalantarapranahara Marma, embodies a delicate balance of Soumya and Agneya qualities, with their interplay dictating the trajectory of life. The precise location of Katikataruna Marma is explored across references, positioned either beside the vertebral column or above the Sphik on the Shronikarna. Anatomically, this Marma amalgamates diverse components: muscular elements such as the gluteal and pelvic muscles, vascular intricacies involving the internal iliac artery, neural and connective structures like sacro-iliac ligaments and lumbo-sacral nerves, skeletal components comprising the iliac bone and sacrum, and the pivotal sacro-iliac joint. Critical insights emerge regarding the aftermath of injuring the Katikataruna Marma. A disruption in the equilibrium of Soumya and Agneya Guna triggers a gradual decline, with blood loss (Shonita kshaya) inducing symptoms like anemia, pallor, malaise, and ultimately, mortality. Prognosis unfolds, emphasizing the manifestation of Pandu, Vaivarna, and Hina Rupa, elucidating the complex interplay between components in the Marma region. By dissecting the intricacies of the Katikataruna Marma, this article contributes to a deeper comprehension of Ayurvedic principles and their holistic approach to wellness. The exploration of Marma points transcends anatomical facets, resonating with Ayurveda’s holistic philosophy of harmonizing physical, mental, and spiritual well-being.